O fenómeno e os seus impactos no desenvolvimento económico e social, Afinal.... O que é o Populismo? - Almeida, E. C. (Figuras & Negócios, 2023)
Abstract: Brief summary introduction: What is “populism”, so prominent in recent times, and which has had – and will continue to have – relevant characters in international political life, such as former North American presidents Donald Trump, and the Brazilian Jair Bolsonaro, or politicians like the French Marine Le Pen, the pro-Brexit Brit, Nigel Farage, and the Italian Beppe Grillo, or government leaders like the Bolivian Evo Morales or the Hungarian Viktor Orbán. And what characterizes them all that leads them to receive the epithet of “populists”? Let us begin by characterizing what Populism is. Over many years, there have been several theses that characterize it as a political current; some welcoming it as a positive factor for political and democratic freedom, others considering it dangerous for the democratic system...